Pengembangan Lagu Kreasi Tematik Berbasis Kognitif pada Perkembangan Anak Usia Dini di Taman Kanak-Kanak - Arinalhaq, Ririen; Yeni, Indra; Ismet, Syahrul; Saridewi, Saridewi (Universitas Negeri Padang, 2020)
This study aims are creating of a thematic creation song at early childhood for children’s cognitive development in kindergarten. There are two songs developed in accordance with the theme of animals sub theme land animals and theme plant sub theme wild plants. Type of the research is Research and Development (R and D) in accordance with the design forward by Plomp consitsts of three phases : prelimenary research, development/ prototyping phase and assassement phase. Assassement phase limited to levels One to One, so this research can provided information about the validity dan practicality of the product. Data on validity was obtain from music, media and subject matter axperts from Department of PG PAUD FIP Universitas Negeri Padang, and information about practicality taken from Teacher of Kindergarten. Data analysis techniques are combination of qualitative analysis and quantitative analysis, which qualitative analysis used at prelimenary research and development/prototyping phase, and quantitative analysis uses percentage statistics. The result of the study are (1) the validity of product is 87.79% in the category of very valid, and (2) The practicality of product is 83.75% in the category of very practical. Finaly as the conclussion of this study is: The Thematic Creation Song Based on Cognitive Development as the product of this study valid dan practical for Chilhood at kindergarten.